Nonclinical evaluation of HS630, a proposed biosimilar of trastuzumab emtansine: affinity, pharmacokinetics, and immunogenicity - Jiang, Hui; Che, Jinjing (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study is to evaluate the similarity of affinity, pharmacokinetics, and immunogenicity shared by HS630 and trastuzumab emtansine (T-DM1).MethodsIn vitro, affinity was tested using a Biacore™ T200 apparatus. In vivo studies were conducted on tumor-bearing mice and cynomolgus monkeys in the context of different dosages and frequencies of administration. Double-antibody sandwich enzyme-linked immunosorbent assay (ELISA) was used to determine the concentration of total antibody (including naked antibody and antibody–drug conjugate (ADC)) and the ADC of HS630 and Kadcyla®. Furthermore, HPLC–MS/MS was used to determine the concentration of free DM1. The bridge ELISA method was performed to determine anti-drug antibody for immunogenicity analysis.ResultsIn vitro, HS630 and Kadcyla® exhibited similar binding affinities for human epidermal growth factor receptor 2 (HER2), with KD values of 6.372 E-11M and 9.424 E-11 M, respectively. After injecting 10 mg·kg−1 of HS630 and Kadcyla® into tumor-bearing mice, the concentration of total antibody and ADC in serum reached its peak concentration at 5 min, and the concentration of total antibody reached its peak concentration at 24 h in the tumor. Meanwhile, in cynomolgus monkeys, the concentration of total antibody and ADC of HS630 exhibited non-linear pharmacokinetic characteristics following a single intravenous administration of HS630 at 0.33 mg·kg−1, 1 mg·kg−1, and 3 mg·kg−1, respectively. No significant drug accumulation was observed after continuous intravenous administration of 3 mg·kg−1 HS630. Biosimilarity evaluation showed that HS630 met the criteria for Cmax and AUC(0-t) geometric mean ratios with Kadcyla® in the serum of tumor-bearing mice, as well as tumors and serum of cynomolgus monkey. No anti-drug antibody was detected in the serum samples obtained from cynomolgus monkeys after intravenous administration of HS630 and Kadcyla®.ConclusionHS630 and originator drug Kadcyla® exhibit pharmacokinetic similarity in tumor-bearing mice and cynomolgus monkeys following intravenous infusion. The comprehensive nonclinical evaluations of this study provide robust evidence for regulatory approval, in addition to addressing of key scientific and technical challenges in biosimilar development.